1992
DOI: 10.1002/jor.1100100115
|View full text |Cite
|
Sign up to set email alerts
|

Angular deformities and forearm function

Abstract: Angular deformities were created in cadaver forearms at proximal, middle, and distal third levels of the radius and ulna separately, and at middle and distal third levels of both bones, to determine the corresponding limitations of pronation and supination. The ranges of pronation and supination were recorded using a rotational motion measurement apparatus instrumented with a 360 degrees goniometer. These experimental results were compared to data obtained from clinical and radiographic examination of 105 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 14 publications
(4 reference statements)
3
61
0
2
Order By: Relevance
“…13,46,47 Up to 10° of angulation is associated with an acceptable limitation of rotation, and loss of 20° of forearm rotation is still compatible with good function. 48 It has been shown that anatomical alignment by operative intervention does not guarantee full return of movement. 32 In our study, all patients had angular deformities of less than 10° in both the AP and lateral radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…13,46,47 Up to 10° of angulation is associated with an acceptable limitation of rotation, and loss of 20° of forearm rotation is still compatible with good function. 48 It has been shown that anatomical alignment by operative intervention does not guarantee full return of movement. 32 In our study, all patients had angular deformities of less than 10° in both the AP and lateral radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In our series of patients, there was evidence of a posttraumatic contracture of the interosseous membrane, because in numerous instances, the tension exerted by the interosseous membrane on the forearm bones did not permit correction of the bone deformity. Thus, release already was warranted to achieve the planned reduction after osteotomy as reported in experimental studies [24,33]. No clinical instability symptoms, statistically significant loss in grip strength, or occurrence of postoperative synostosis occurred in our patients after interosseous membrane release with respect to patients without membrane release.…”
Section: Discussionmentioning
confidence: 49%
“…Combined angular deformities of the radius and ulna in different directions reduce substantially more ROM than combined angulation in the same direction [37]. Proximal deformities had less impact on ROM than equivalent deformities produced at the middle or the distal third of the radius [33]. Similarly, several investigations assessed the effect of experimental axial malunions of the radius and ulna on pronation and supination [12,19,37,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Work by Sarmiento et al, 7 Matthews et al, 8 and Tarr, Garfinkel and Sarmiento 9 have shown that, except in very young children, residual angulation of the forearm greater than 10° should be corrected since remodelling is unpredictable. 10,11 Angulation has been shown to affect the range of pronation and supination of the forearm.…”
mentioning
confidence: 99%